‘Sunt quadraginta anni vel circa’: Southern French Waldensians and the Albigensian crusade - Taylor, Claire (Oxford University Press, 2018)
This paper contributes new evidence and a new perspective to the study of the religious heresy known as Waldensianism in the high-medieval Languedoc, and its relationship to both orthodox authority and the ‘Cathar’ heresy. Although they were outlawed by Rome in 1184, Waldensians were operating openly in the Cathar lands pertaining to the viscounts of Béziers and the counts of Toulouse and Foix-with clerical complicity. This was until the Albigensian Crusade (1209-29). Its northern French army attacked Cathars and their noble supporters, but began executing Waldensians too. This paper offers a precise chronology and demography for these processes of toleration and persecution. For the first time, it reveals that from 1209, Waldensian refugees re-located beyond the warzone, fleeing to the County of Rodez, the north of the County of Quercy, and the Duchy of Gascony, and were no longer to be found in the Cathar heartlands. In doing this, it sheds light on the wider process of suppressing minority religious groups in the high middle ages, particularly their social and geographical dislocation and assimilation. It also contributes to the related historiographical debate concerning the nature of heresy in medieval Languedoc more generally.